First-generation college students : understanding and improving the experience from recruitment to commencement - Ward, Lee, Dr.; Siegel, Michael J.; Davenport, Zebulun; Gardner, John. (San Francisco : Jossey-Bass, 2012)
"As more and more of the college-going population is made up of those who are the first in their families to attend college, institutions need to find ways to help these students succeed if they expect to maintain enrollments. This groundbreaking resource explores the challenges and barriers to first-generation students and offers a wealth of helpful recommendations for helping these students succeed in their academic careers. This book helps leaders in academic and student affairs to understand these special challenges and how best to meet them"--
Includes bibliographical references and index.
Keywords: First-generation college students -- United States; People with social disabilities -- Education (Higher) -- United States; College student orientation -- United States; College student orientation; First-generation college students; People with social disabilities -- Education (Higher); United States